The Multifaceted Impact of COVID-19 on Social Media Users' Wellbeing and Relationship With Urban Nature - Johnson, Michelle L.; Sachdeva, Sonya S. (Frontiers in Sustainable Cities, 2022)
As the COVID-19 pandemic has unfolded, recognition of the value of urban nature has risen in the media and increases in use have been observed. In cities, where people often lack access to private greenspaces, parks and other urban greenspaces offer opportunities for exercise and physically distanced socializing. Previous research has demonstrated the benefits of urban greenspaces to both physical and mental health, during times of relative stability. Here, we seek to examine how people’s responses to greenspace are affected by a global pandemic, which uniquely affects both physical movements and mental wellbeing in the population at large. We compare tweets focused on nature- and greenspace-related keywords and hashtags from March to July 2019 with tweets from the same period in 2020. We also examine the influence of stay-at-home restrictions in 2020. These posts reinforce findings from conventional survey approaches showing that people’s relationship to greenspace is multifaceted. Furthermore, the results of our pre-post analysis of people’s outdoor use suggest that the pandemic has had a differential impact on these multi-faceted dimensions of people’s engagement with nature. By applying a multidimensional construct of wellbeing like PERMA, we are able to identify positive emotion, positive relationships, and meaning as subcomponents of wellbeing that can potentially be increased by urban nature. These findings are important in demonstrating that greenspace in cities is playing a critical role in individuals’ resilience and wellbeing during the early months of the pandemic and highlight the need for maintaining and expanding access to urban greenspaces in the future, for the benefit of all city residents.